NEW SOCIAL MOVEMENTS, POLITICAL AND ETHNIC REGIONAL SPEECH IN ANGARAES, HUANCAVELICA - Plasencia Soto, Rommel (2014)
An important item idea is that of ethno-political, when a group or movement thinks its cultural attributes is the subject of discrimination or when using the ethnic identity (a term more restricted than that of culture) to participate in political competition and obtain advantages and resources of society. The Peruvian case is no exception.